Re-orienting geographies of urban diversity and coexistence: Analyzing inclusion and difference in public space - Ye, Junjia (Progress in human geography, 2019)
Much has been said about diversity and coexistence in public spaces, but there remains a silence on the very nature of incorporation within the spatial negotiations and transformations these involve. This paper examines the spatial and political implications of inclusion by identifying two key strands of geographical imaginations on urban diversity: co-presence and togetherness and the incorporation of difference and diversity in everyday shared spaces. I aim to retain critical analytical purchase on what living with difference in shared spaces – specifically through ‘inclusion’ – means. Focusing on Asian urban contexts, I illustrate how measures of inclusion can carry out the political work of what form belonging takes and, consequently, who does and does not belong in diversifying cities. Conceptually, this demonstrates how, in the Asian context, the politics of urban diversification are intertwined with the politics of labour to the extent that diversity in everyday shared spaces is shaped by the structuring of migrant labour incorporation.